2018
DOI: 10.1002/ptr.6202
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid‐rich fraction of Bauhinia forficata Link leaves prevents the intestinal toxic effects of irinotecan chemotherapy in IEC‐6 cells and in mice

Abstract: This study evaluated the effects of flavonoid-rich fraction from Bauhinia forficata leaves (FRF-BF), against intestinal toxicity induced by irinotecan. The leaves of this plant are used like tea in Brazilian folk medicine, and it is rich in flavonoids, mainly kaempferitrin.First, the chemopreventive effects of FRF-BF and kaempferitrin were evaluated in intestinal cells (IEC-6 cells) exposed to irinotecan. Next, the effects were evaluated against irinotecan-induced mucositis in mice. Lastly, melanoma was induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…However, the results are not consistent among the studies involving chemoprevention treatments. Studies performed by Cheah et al [31] and Cechinel-Zanchett et al [32], for example, demonstrated that flavonoids could not prevent the progressive weight loss induced by chemotherapy, even though their efficacy was shown in reversing histological changes, oxidative stress, and inflammatory process induced during mucositis. Weight loss is a side effect caused by the activation of inflammatory responses followed by gastrointestinal dysfunction [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results are not consistent among the studies involving chemoprevention treatments. Studies performed by Cheah et al [31] and Cechinel-Zanchett et al [32], for example, demonstrated that flavonoids could not prevent the progressive weight loss induced by chemotherapy, even though their efficacy was shown in reversing histological changes, oxidative stress, and inflammatory process induced during mucositis. Weight loss is a side effect caused by the activation of inflammatory responses followed by gastrointestinal dysfunction [33].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic success and quality of life of the cancer patient also depend on an early diagnosis and management of the complications of anticancer therapy. Nowadays, different strategies are used to treat mucositis and, among them also products from natural sources, which possess anti-apoptotic, anti-inflammatory and antioxidant properties [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the role of kaempferitrin in vasorelaxation in NTR and SHR aortic rings, and both 3 and its aglycone, kaempferol (0.001-0.3 µg/mL), were able to induce vasorelaxation by 34.70 % and 40.54 %, respectively [57]. There have been few studies on the toxic potential of this compound, but in vitro investigations have shown that despite being cytotoxic to cancer cell lines [58], kaempferitrin did not exert any toxicity in intestinal epithelial cells (IEC-6 lineage) [59].…”
Section: Isolated Compounds From Brazilian Medicinal Plants With Diurmentioning
confidence: 99%